Phosphoproteomic Profiling Reveals Early Salt-Responsive Mechanisms in Two Foxtail Millet Cultivars - Pan, Jiaowen; Li, Zhen; Wang, Qingguo; Guan, Yanan; Li, Xiaobo; Huangfu, Yongguan; Meng, Fanhua; Li, Jinling; Dai, Shaojun; Liu, Wei (Frontiers in Plant Science, 2021)
Excess soluble salts in saline soils are harmful to most plants. Understanding the biochemical responses to salts in plants and studying the salt tolerance-associated genetic resources in nature will contribute to the improvement of salt tolerance in crops. As an emerging model crop, foxtail millet (Setaria italica L.) has been regarded as a novel species for stress resistance investigation. Here, the dynamic proteomic and phosphoproteomic profiling of two foxtail millet varieties of An04 and Yugu2 with contrasting salt tolerance characteristics were investigated under salt stress. In total, 10,366 sites representing to 2,862 proteins were detected and quantified. There were 759 and 990 sites corresponding to 484 and 633 proteins identified under salinity in An04 and Yugu2, respectively, and 1,264 and 1,131 phosphorylation sites corresponding to 789 and 731 proteins were identified between these two varieties before and after salt stress, respectively. The differentially-regulated phosphoproteins (DRPPs) were mainly involved in signal transduction, regulation of gene expression, translation, ion transport, and metabolism processes. Yugu2 possessed signal perception and transduction capabilities more rapidly and had a more intense response compared with An04 upon salinity. The sucrose metabolism pathway, in particularly, might play a vital role in salt response in foxtail millet, which not only provides UDP-glucose for the cellulose synthesis and energy production, but also promotes flavonoid related synthesis to enhance the salt tolerance ability. Over-expressing the phospho-mimic sucrose synthase (SuS) (SuSS10D) in soybean roots enhanced salt tolerance compared with over-expressing SuS lines. The knowledge of this research will shed light on elucidating the mechanisms of salt response, and pave the way for crop varieties innovation and cultivation under salinity and stresses.